2019
DOI: 10.3389/fchem.2019.00485
|View full text |Cite
|
Sign up to set email alerts
|

Modified Particle Swarm Optimization Algorithms for the Generation of Stable Structures of Carbon Clusters, Cn (n = 3–6, 10)

Abstract: Particle Swarm Optimization (PSO), a population based technique for stochastic search in a multidimensional space, has so far been employed successfully for solving a variety of optimization problems including many multifaceted problems, where other popular methods like steepest descent, gradient descent, conjugate gradient, Newton method, etc. do not give satisfactory results. Herein, we propose a modified PSO algorithm for unbiased global minima search by integrating with density functional theory which turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 154 publications
(129 reference statements)
0
26
0
1
Order By: Relevance
“…DFT-PSO adjusts each particle's trajectory at every time stamp while following the convergence criteria. We have successfully implemented these techniques to find the GM configurations for small-sized nonmetallic clusters such as Boron (B 5 and B 6 ) (Yuan et al, 2014), Carbon (C 5 ) (Jana et al, 2019), and polynitrogen clusters (N 4 2and N 6 4-) (Mitra et al, 2021), and metallic clusters such as Al 4 2- (Mitra et al, 2020), Au n (n 2-8), and Au n Ag m (2 ≤ n+m ≤ 8) (Mitra et al, 2021).…”
Section: Global Optimization Using Machine Learning Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…DFT-PSO adjusts each particle's trajectory at every time stamp while following the convergence criteria. We have successfully implemented these techniques to find the GM configurations for small-sized nonmetallic clusters such as Boron (B 5 and B 6 ) (Yuan et al, 2014), Carbon (C 5 ) (Jana et al, 2019), and polynitrogen clusters (N 4 2and N 6 4-) (Mitra et al, 2021), and metallic clusters such as Al 4 2- (Mitra et al, 2020), Au n (n 2-8), and Au n Ag m (2 ≤ n+m ≤ 8) (Mitra et al, 2021).…”
Section: Global Optimization Using Machine Learning Techniquesmentioning
confidence: 99%
“…Various models/empirical potentials (EPs) such as Lennard-Jones (LJ), Born-Mayer, Sutton-Chen, Gupta and Murrell-Mottram potentials can effectively explain the bonding within various clusters. A number of studies performed by Chattaraj et al reveal that PSO is more efficient than commonly used techniques such as GA, SA, and BH for finding the GM of small clusters (Mitikiri et al, 2018;Jana et al, 2019). Further developments over PSO algorithm have been accomplished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where c 0 is an inertial parameter affecting the movement propagation given by last velocity value, and two acceleration coefficients c 1 and c 2 , respectively, are the importance of personal best value and the importance of social best value; rand 1 and rand 2 are two random numbers between [0, 1]. Shi and Eberhart [21] indicated that choosing c 0 ϵ [0.8, 1.2] results in faster convergence, hence, in this study, we set c 0 = 1. Generally, c 1 and c 2 are set to 2.…”
Section: Pso-based Parameters Determiningmentioning
confidence: 99%
“…Since the numbers of local minima grow quickly with the size of clusters, the global optimization becomes a very difficult task to overcome. Thus, different search algorithms and methodologies, including the genetic algorithm (GA) (Hartke, 1993;Deaven and Ho, 1995;Hartke, 1995;Daven et al, 1996;Rogan et al, 2013;Kanters and Donald, 2014;Shayeghi et al, 2015;Lazauskas et al, 2017;Rabanal-León et al, 2018;Jäger et al, 2019;Yañez et al, 2019) and relative evolutionary algorithm (EA) (Zhou et al, 2020), the swarm intelligence algorithm (Wang et al, 2012;Jana et al, 2019) and others, have been proposed and applied in the past decades (Zhang and Glezakou, 2020).…”
Section: Introductionmentioning
confidence: 99%